Case Report: Rare Dynein Axonemal Heavy Chain 9 Mutations in a Han-Chinese Patient With Kartagener Syndrome - Feng, Jingjing; Li, Junqing; Du, Yong; Shi, Tianyun; Sharma, Lokesh; Jie, Zhijun (Frontiers in Medicine, 2022)
A 52-year-old woman presented with respiratory symptoms of productive cough and shortness of breath. She had suffered from repeated bacterial pneumonia. Her clinical and imaging findings revealed chronic sinusitis, tree bud signs in pulmonary imaging and situs inversus. We suspected Kartagener syndrome of primary ciliary dyskinesia (PCD) and performed a genetic examination. The compound heterozygous mutations of dynein axonemal heavy chain 9 (DNAH9) was detected, which encoded outer dynein arms (ODAs) components. DNAH9 mutation is a relatively rare event in PCD, and this is the first report of PCD patients with DNAH9 mutation in Chinese population. In addition to this, the literature review was conducted.